Metodologi Periwayatan Hadis Musalsal: Analisis Deskriptif terhadap Kitab Jiyâd al-Musalsalât karya Jalal ad-Din as-Suyuthi (849 - 911 H) - Khoirul Anam; Alwi Bani Rakhman; Suciadi Ramadlan; Mustofa Mustofa; Mohammad Maimun (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the methodology of transmitting musalsal hadith according to as-Suyuthi's view in one of his works, Jiyâd al-Musalsalât. The formulation of the problem posed focuses on two issues, namely regarding the background of the compilation and compilation of the book and the method of transmitting the Musalsal hadith based on qualification criteria according to as-Suyuthi. This study used a qualitative method with the source and processing of library data with content analysis. The results of the research analysis conclude first, the background of the collection and compilation of musalsal hadiths by as-Suyuthi is apart from being spiritually motivated because of his great attention to the maintenance of hadiths complete with information on sanads and those related to them. Then secondly, in compiling the Jiyâd al-Musalsalât, as-Suyuthi selected the hadiths with the best quality in his view on each theme. This shows the meaning that not all of the Musalsal hadiths he narrated are of strong quality (shahih or hasan), but the best ones are in the chapter or theme, even if the quality is dhaif.